Menuju Real Time Processor Dengan Algoritma Multioperand Minimax MSB-First Addition - Kapiudin, Maulani (Lembaga Penerbitan Universitas Esa Unggul, 2008)
Aritmatic operationÃ¢â‚¬â„¢s executation time in real time system is bounded by deadline. The method commonly used to meet these deadline is by employing any suitable process scheduling algorithm. These effort contains potential weakness, that is if time needed to operate is longer than its deadline, the final result can not be determined. This is caused by the algoritms of the arihtmatic operation commonly used nowday can determine a final result after completing computation or accuracy of computation equal to 100%.. Ã‚Â This research tries to design new algorithm and its processing unit that works to fulfilled real time principles. i.e Minimax Computation whish start its computation process from the digit with highest value and the final result can be determined before completing all the process of computation. Minimax Computation consist of two unit MSB-First Addi-tion and one unit of decision Making. Result from two unit MSB-First Addition will be compared by unit of Decision Masking if their quality result equal. This unit will decide the final result. The result of testing to This unit Minimax Computation provide the final result of computation can be determined before completion all of the computationÃ¢â‚¬â„¢s process.Keywords: MSB-First Addition, Minuimax, Computation